Mitigation of harmonic distortion using shunt active power filter / Muhd Kamal Ashraf Mat Nasir - Mat Nasir, Muhd Kamal Ashraf (2010)
In recent years, the usage of power electronics equipments continues to increase, due to the increased usage of nonlinear loads and distributed power sources. These nonlinear loads draw non sinusoidal current from the mains to generate harmonics and reactive currents, which lead to low power factor, low energy efficiency, low power capacity, and harmful disturbance to other appliances. These harmonic and reactive currents will distort the voltage at the point of common coupling, reducing the quality of power delivered on the network. This paper presents a Shunt Active Power Filter (APF) which focuses on mitigating the harmonic distortion.